Problem z podmiotowością prawnomiędzynarodową Palestyny - Stępień, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The paper concerns the legal status of Palestine as a subject of international law. To some extent Palestine is the edge case of statehood in international law. In a sense, we are witnessing the forging of the international status of Palestine in real-time. For some scholars Palestine is a state, while for others it is not. It is quite a common trope in discussions concerning the status of Palestine to underline how many states have recognized Palestine and established diplomatic relations with it. The problem is that while principle of tertium non datur seems to be applicable in case of recognition of Palestine, the reality is more complex. Some states indeed recognized Palestine, but not as a state but as a non-state subject of international law. A closer examination of the diplomatic relations of Palestine reveals that they are more akin ones maintained with a non-state subject the relations than with a state. By way of analogy, the international status of Palestine seems to be similar to one of Holy See—that is the case of Palestine’s “non-member state” status of in the UN, which is analogous to the status of Holy See. At the same time, Palestine is a state from point of view of the ICC, a least in context of the Rome Statute. The jurisdiction of the ICC depends on notion of state territory, after all. But effective control of territory by Palestine is in doubt, thus the in its case the ICC applied the construct of “occupied territory.” Thus Palestine seems to be a state whose territory is being occupied by Israel. That is also confirmed by the ICJ. As such, Palestine is not just a state—it is an occupied state, a state in statu nascendi or a non-state subject of international law. The issue of which of these descriptions is the most appropriate notwithstanding, they all share one common denominator: the international subjectivity of Palestine is detached from effective control of territory. While the very notion of state in international law sits somewhere between Kelsenian “is” and “ought,” the latter is significantly more pertinent for Palestine. Part of the international community is eager to treat Palestine as state but that decision is not an abstract and general one. Treating Palestine as a state is motivated by a single goal—granting it particular rights and privileges reserved for states. The non-member state status of Palestine in the UN is not based on the general recognition of Palestinian statehood—its participation in works of the UN is at stake. In that context Palestine’s membership in UNESCO is something of a breakthrough. Since its finalization Palestine become a state according to so-called Vienna Formula—thus Palestine acceded to key UN conventions. And yet Holy See is also party to some of them. Palestine’s status within of international community illustrates the issues caused by the decentralized recognition of states quite succinctly. In the case of Poland, recognition of Palestine is an outcome of decision of authoritarian government of Polish People’s Republic. That decision was the effect of relations between Poland and Israel and dependence of Poland upon the totalitarian Soviet Union. However that act of recognition of Palestine was not a recognition of its statehood.
Keywords: prawo międzynarodowe; pojęcie państwa; uznanie państwa; efektywność w prawie międzynarodowym; wpływ autorytaryzmu na stosunki międzynarodowe Polski